Analysis Of The Relationship Between Risk And Return Using The Capital Asset Pricing Model (Capm) Method At Kompas 100 - Andini Nurwulandari (Institute of Computer Science (IOCS), 2021)
The risk-reward trade-off implies that risky investments should demand a premium over risk-free returns. It is critical to managing to change investment opportunities to maintain a healthy risk-reward relationship. This thesis employs a quantitative model in conjunction with a descriptive research strategy. This is a quantitative study using an analytic-descriptive approach. The sample size for this analysis is 100 Kompas. The data source is secondary sources from IDX publications. For four years, the data set contains the closing price of shares and the IHSG (1 January 2016 - 31 December 2019). The Rate of Return on Shares (Ri), Market Returns (Rm), Risk-Free Returns (Rf), Systematic Risk, Expected Return E (Ri), and the Relationship between Risk and Return with CAPM using Pearson Correlation are used to analyze the data. The results of the correlation coefficient test indicate that: 1) The sample used in the CAPM calculation exhibits a strong positive relationship between beta and the CAPM expected return. As beta increases, the predicted return increases proportionately and vice versa. If beta decreases, the expected return decreases; and 2) From the 52 study samples, 33 company stocks fall into the productive stock category, and 19 falls into the inefficient stock category.